Mrs. Pollifax on safari - Gilman, Dorothy, 1923-2012 (Doubleday, 1977)
At the request of her old CIA contact, Carstairs, Emily Pollifax leaves New Jersey and her geraniums for Africa, where she battles dark forces of evil to save an African leader from assassination.